Professional Skills and Competences of Technology Teachers - Aripov Ikhtiyar Yusupovich- (International Journal on Integrated Education, 2023)
Teaching folk handicrafts to young people is a way to learn life through observation, to observe character, abilities, and moods, to introduce, introduce, and interest students to the world of professions, as well as students with abilities and inclinations. is considered a factor that creates the ground for conscious career choices.